2021
DOI: 10.1186/s12866-020-02072-3
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the molecular basis association between promoter polymorphisms of the IL1B gene and Helicobacter pylori infection in the Sudanese population: computational approach

Abstract: Background Helicobacter pylori (H. pylori) infects nearly half of the world’s population with a variation in incidence among different geographic regions. Genetic variants in the promoter regions of the IL1B gene can affect cytokine expression and creates a condition of hypoacidity which favors the survival and colonization of H. pylori. Therefore, the aim of this study was to characterize the polymorphic sites in the 5′- region [−687_ + 297] of IL1B in H. pylori infection using in silico tools… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…For histological investigation, the biopsies were preserved in 10% formalin. DNA extraction was performed by using innuPREP DNA Mini Kit (analytikjena AG, Germany) and followed the protocol that was given by the manufacturer, as previously described in[ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For histological investigation, the biopsies were preserved in 10% formalin. DNA extraction was performed by using innuPREP DNA Mini Kit (analytikjena AG, Germany) and followed the protocol that was given by the manufacturer, as previously described in[ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two sets of primers were used in PCR with confronting two-pair primer to detect the TNF-A -1030 C/T polymorphism as follow: for allele T, the sequences of the primers were F: 5'-AAGGCTCTGAAAGCCAGCTG-3' and R: 5'-CCAGACCCTGACTTTTCCTTCA-3'; and for allele C, F: 5'-GAAGCAAAGGAGAAGCTGAGAAGAC-3' and R: 5'-CTTCCATAGCCCTGGACATTCT-3'[ 54 ]. The PCR mixture components were the same as in[ 30 ]. The amplification conditions were initial denaturation at 95 °C for 10 min, followed by 30 cycles of denaturation at 95 °C for 1 min, annealing at 66 °C for 1 min, extension at 72 °C for 1 min and final extension at 72 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The complex interrelationship between these cytokines, H. pylori infection and IL-1β was emphasized by a study performed on acute coronary syndrome patients, where it was shown that the coexistence of H. pylori -seropositivity and certain IL-1β polymorphisms is associated with higher levels of high-sensitivity CRP, resulting in an increased risk of ST-segment elevation myocardial infarction [ 81 ]. In addition, genetic variants in the promoter regions of the IL-1β gene were recently shown to alter cytokine expression, creating a hypoacidity environment involved in enabling the long-term persistence and colonization of H. pylori [ 82 ]. Nevertheless, the influence of IL-1β gene polymorphisms on H. pylori infection might be closely related to ethnicity or geographical area [ 83 ].…”
Section: The Trialogue Between H Pylori Cytokines...mentioning
confidence: 99%
“…Genetic variants in the promoter regions of the IL-1β gene → alter cytokine expression → a hypoacidity environment involved in enabling long-term persistence and colonization of H. pylori [ 82 ]…”
Section: The Trialogue Between H Pylori Cytokines...mentioning
confidence: 99%
“…1,2 It has been associated with the development of various clinical disorders of the upper gastrointestinal tract, such as aseptic ulcers, chronic gastritis, gastric adenocarcinoma and gastric mucosa-associated lymphoid tissue (MALT) lymphoma, which is classified as type I cancer-causing agent by the World Health Organization (WHO). [3][4][5] Its distribution is worldwide and affects more than 90% of the world population, but it is more common in developing countries with the highest prevalence found in Africa, 6,7 probably due to the possible transmission through the fecal-oral route and the unsafe sanitation conditions in these countries. 1,8 Clinically, a variety of various invasive techniques (requiring endoscopy and biopsy which include, culture, histological examination, and rapid urease test, CLO (Campylobacter like organism) test, smear examination, and molecular studies) or noninvasive techniques (including serology, respiratory urea breath test, or the detection of fecal antigen) are often performed to detect H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%